Did the post war repatriation of Lebanese physicians drive recent Lebanese medical graduates to emigrate? An observational study - Maroun Nancy; El-Asmar Khalil; Akl Elie A; Adib Salim M; Khater-Menassa Beatrice (BMC, 2008)
Abstract Background A significant number of Lebanese medical graduates have emigrated from Lebanon. The objective of this study was to evaluate the hypothesis that the repatriation of Lebanese physicians educated abroad has contributed to the international emigration of recent Lebanese medical graduates. Methods We analyzed the demographic and educational characteristics and the year of registration of physicians registered with the two physician associations in Lebanon as of 2007. We then analyzed the number of new and total registrants and the physician density for the years 1977-2006. Finally we calculated the percentage of Lebanese graduates of the years 1977-2006 registered as of 2007. Results As of 2007, 10,918 physicians were registered in Lebanon. Most were male (80.4%) and graduated from either Lebanese (36.4%) or Eastern European (30.6%) medical schools. The top three regions of specialty training were Western Europe (31.8%), Eastern Europe (28.4%) and Lebanon (25.7%). About half the physicians registered with the Lebanese Order of Physicians as of 2007 joined during the 1990s decade; only 26.2% of these graduated from Lebanese medical schools during that decade. The number of new registrants increased dramatically in the early 1990s and started decreasing in the early 2000s. About 60% of Lebanese medical graduates of the years 1977-2006 were registered in Lebanon as of 2007. Categorizing Lebanese medical graduates by their year of graduation, the percentage registered in Lebanon as of 2007 showed a "dip" for those who graduated in the early 1990s. Conclusion The high number of physicians educated abroad returning to Lebanon after the end of the civil war may have driven recent Lebanese medical graduates to emigrate.